Perioperative Pain Management With Bilateral Pecto-intercostal Fascial Block in Pediatric Patients Undergoing Open Cardiac Surgery - Zhang, Yang; Min, Jia; Chen, Shibiao (Frontiers in Cardiovascular Medicine, 2022)
Purposes: Pediatric open cardiac surgical patients usually suffer from acute pain after operation. The current work aimed to explore the impact of bilateral PIFB in children suffering from open cardiac surgery. Methods. This work randomized altogether 110 child patients as bilateral PIFB (PIF) and non-nerve block (SAL) groups. This work adopted postoperative pain at exercise and rest statuses as the primary endpoint, whereas time-to-drain removal/extubation/initial defecation, intraoperative/postoperative fentanyl use, and length of ICU and hospital stay as the secondary endpoints. Results. MOPS were significantly higher at 24-h postoperatively at coughing and rest statuses in SAL group compared with PIF group.Meanwhile, PIF group exhibited markedly lower intraoperative/postoperative fentanyl use amounts, as well as markedly reduced time-to-extubation/initial flatus, and length of ICU/hospital stay. Conclusion. Bilateral PIFB in pediatric open cardiac surgical patients provide effective analgesia and lower the length of hospital stay .